MEDIA DAN EVANGELISM - Ruth Ravika Sari; Royke Siahainenia; Erikson Sumtaky (Universitas Kristen Satya Wacana, 2013)
Onecubed is an evangelism television program focused on youth in Indonesia. This program produced by CBN (Cahaya Bagi Negeri) and broadcasted by GlobalTV, an Indonesia television channel. CBN has a vision that this program can effectively evangelized the youth in Indonesia, at the same time, Global TV aims to reach a high rating by broadcasting such programme. In reality, evangelism programme doesn’t give much rating. By knowing this information this research made in Van Djik crtitical analition. Based on this information, this research aimed to understand the construction of evangelism television programme by analizing the texts provided in to youth. Related themes during june-juli 2012. Van Dijk critical discourse analysis method is being used to explore the construction structure and its meaning. This findings of the study provide explanations on the formation of youth evangelism programme in Indonesia, that give perspectives to understand media relations (media power) in the context of political economy of media. This study also underlined the importance of youth evangelism television programme as a “serious” programme that can not be underestimated, eventhough its been frawed with entertainment approaches. Keywords: Youth Televangelism in Indonesia, Critical Discourse Analysis, Political Economy of Media, Cahaya Bagi Negri (CBN).